2016
DOI: 10.1007/s10548-016-0493-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Focal Epileptogenic Networks in Generalized Epilepsy Using Brain Functional Connectivity Analysis of Bilateral Intracranial EEG Signals

Abstract: Simultaneous bilateral onset and bi-synchrony epileptiform discharges in electroencephalogram (EEG) remain hallmarks for generalized seizures. However, the possibility of an epileptogenic focus triggering rapidly generalized epileptiform discharges has been documented in several studies. Previously, a new multi-stage surgical procedure using bilateral intracranial EEG (iEEG) prior to and post complete corpus callosotomy (CC) was developed to uncover seizure focus in non-lateralizing focal epilepsy. Five patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…2 Under this circumstance, the corpus callosum is considered to be a major pathway of seizure propagation in the bilateral epileptic network, which might have different configurations from nonfocal bilateral synchronization. 3 The results of DTI analysis in this study demonstrated that the corpus callosum suffered more structural damage related to demyelination in the lateralized group than in the nonlateralized group, causing reduced FA and increased RD. 4 This finding further indicates that different configurations of bilateral epileptic networks exist in generalized epilepsy with greater or less reliance on the corpus callosum, which inflicts varied structural alterations along their respective pathways.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…2 Under this circumstance, the corpus callosum is considered to be a major pathway of seizure propagation in the bilateral epileptic network, which might have different configurations from nonfocal bilateral synchronization. 3 The results of DTI analysis in this study demonstrated that the corpus callosum suffered more structural damage related to demyelination in the lateralized group than in the nonlateralized group, causing reduced FA and increased RD. 4 This finding further indicates that different configurations of bilateral epileptic networks exist in generalized epilepsy with greater or less reliance on the corpus callosum, which inflicts varied structural alterations along their respective pathways.…”
Section: Discussionmentioning
confidence: 50%
“…eralization. 3,14 In some patients with generalized seizures, focal seizure onset might be discovered following disruption of the rapid propagation between two hemispheres after corpus callosotomy. 2 Therefore, the bilateral epileptic networks in generalized epilepsy with focal onset could have greater reliance on the corpus callosum for seizure propagation than the bilateral epileptic networks in generalized epilepsy with nonfocal bilateral synchronization.…”
mentioning
confidence: 99%
“…Drop attacks are the most disabling feature of LGS and are known to be caused by secondary bilateral synchrony. This rapid spread via the CC explains the efficacy of callosotomy in reducing drop attacks in LGS patients [1,[4][5][6][7][8][9][10].…”
Section: Discussion / обсуждениеmentioning
confidence: 96%
“… 1 Recent network analyses have, however, revealed that these so-called generalized epilepsies are in fact associated with a number of focal abnormalities. 40 …”
Section: Methodsmentioning
confidence: 99%